Strategi Implementasi Corporate Culture Untuk Membangun Etos Kerja yang Produktif di PT. Megah Bangunan Abadi Tulungagung - Wulansari, Devi; Suwarsono, Bambang; Kusumawardhani, Mawar Ratih (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This company is one of the largest construction companies in Tulungagung and has a strong culture to support the achievement of strategic goals and enhance employee performance. The company's culture plays an important role in shaping the behavior, values, and attitudes of employees, which can influence the productivity and performance of the company. This research method uses a descriptive qualitative approach. Data collection was conducted using observation, interviews, and documentation methods at PT. Megah Bangunan Abadi Tulungagung. This study aims to investigate the Corporate Culture Implementation Strategy to build a Productive Work Ethic at PT. Megah Bangunan Abadi Tulungagung. These findings can help identify the implementation strategy of corporate culture, the challenges faced, and the impacts produced. The results of this study indicate that the strategy for implementing corporate culture to build a productive work ethic at PT. Megah Bangunan Abadi Tulungagung requires a deep understanding of the employees and the factors that influence them because PT. Megah Bangunan Abadi has employees with varying levels of education. However, PT. Megah Bangunan Abadi Tulungagung has already implemented open and transparent communication as one of the strategies to strengthen the work ethic. Having a positive organizational culture can reinforce the existing culture within the company, especially if employees feel valued and supported, which can enhance performance, motivation, responsibility, creativity, and loyalty of the employees.